ANALISIS HUBUNGAN PARAMETER LALU LINTAS MENGGUNAKAN MODEL GREENSHIELD DAN MODEL UNDERWOOD (Studi Kasus : Ruas Jalan Gajah Mada, Maumere) - Febbiana Donnathia Demon; Anastasia M. Noralita Soludale; Yono Putra (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2023)
In terms of traffic characteristics and level of service, volume (Q), speed (Vs) and density (D) are interconnected. Jalan Gajah Mada in the city of Maumere is included in the collector road class with a road length of 450m, a road width of 11m which is divided into 2/2 TT. To overcome traffic problems due to the presence of several shopping centers which reduce road performance, knowledge is needed about traffic characteristics and models of the relationship between these characteristics. This research aims to analyze the relationship between traffic parameters that occur. Survey data includes volume (Q) and velocity (Vs) using the manual count method, while model analysis uses Greenshield and Underwood. Volume (Q), speed (Vs) and density (D) of traffic were analyzed based on the 2023 Indonesian Road Capacity Guidelines (PKJI 2023) for Urban Roads. The analysis results show that the highest volume (Q) is 917.70 pcu/hour, the highest speed (Vs) is 41.13 km/hour, and the highest density (D) is 46.29 pcu/hour. From the results of the analysis using the Greenshield and Underwood models, it can be seen that the traffic characteristics that are in accordance with the existing conditions that occur on Jalan Gajah Mada are the Greenshield model with a value of r² = 0.616, with the model equation Vs = 36.091 – (36.091/77.766). D.